Sociobiodiversity and Sovereignty and Food and Nutritional Security as an inseparable right to adequate and healthy food (Research, Society and Development, 2022)
Biodiversity is essential for a decent and fair life. Thus, this study aimed to contextualize sociobiodiversity and Sovereignty and Food and Nutritional Security (SFNS) as an inseparable right to adequate and healthy food. Searches were done on the CAPES Journal Portal, FSTA – Food Science and Technology Science Direct, SciELO, Academic Google, gray literature and the United Nations (UN) portal; Ministry of the Environment – MMA of Brazil, Biodiversity for Food and Nutrition - BFN and specific legislation on the subject studied. The review showed the importance of a healthy and sustainable food systems strategy, through cross-cutting actions as a governance policy to mitigate social injustice, to boost people's economics, to promote actions of biodiversity, sustainability and food and nutrition security as a right to adequate food and healthy to traditional communities, family farmers, agroecological producers and agrarian reform settlers who have the land as their livelihood. In addition, they promote the sustainable environment as a goal for the 2030 SDG, helping humanity to face the global challenges of social injustice as the right to adequate and healthy food.